Analisis Tingkat Efektivitas Kerja pada Mesin Auto Hanger dengan Menggunakan Metode Overall Equipment Effectiveness (OEE) - Melani Magdalena Hutabarat; Ahmad Muhsin (OPSI, 2020)
The packing plant department 1 is still lacking in meeting production productivity targets. Therefore, the availability of raw materials and the condition of machinery and equipment is important to consider so that product productivity can be optimized. Three aspects affect the effectiveness of the machine in the packing department, namely productive time, work speed of the machine, and the quality of the product produced. The purpose of this study is to measure the effectiveness of the auto hanger engine by using the Overall Equipment Effectiveness (OEE) method to obtain the value of availability, performance efficiency, and rate of quality. The results obtained from OEE calculations are expected to be an evaluation of improvements in effectiveness that will be generated in the future. Based on the results of research that overall equipment effectiveness on the three machines has not reached world-class standards, which is> 85%. The availability value on the three machines also still does not meet the world-class standard, which is> 90%. The performance of rate values on the three machines also still does not meet world-class standards, which is> 95%. The availability value on the three machines also still does not meet the world-class standard, which is> 99%.